Prevalence of Drug Interaction in Severely Obese Individuals and Associated Factors: Baseline Results from a Clinical Trial - Ana Carolina Figueiredo Modesto; Erika Aparecida Silveira; Ana Paula dos Santos Rodrigues; Dione Marçal Lima; Mércia Pandolfo Provin; Rita Goreti Amaral (MDPI AG, 2020)
The prevalence of obesity is increasing worldwide and is commonly associated with comorbidities. The use of several drugs is often necessary, which leads to Potential Drug Interactions (PDI) that may increase the morbidity and mortality. This study aimed to analyze the prevalence of drug interaction and its association with socio-demographics, health status, and drug use in severely obese individuals. Baseline data from a randomized clinical trial registered at Clinicaltrial.gov (NCT02463435) were used. A total of 150 individuals aged 18-65 years with a body mass index of 35 kg/m2 were included. The outcome variable was the presence of PDI, and the explanatory variables were divided into the following four levels: socio-demographic, lifestyle, health, and medication use. The prevalence of PDI was 50% (n = 75) (95% CI 41-58). The variables associated with drug-drug interactions in the multiple analyses were arterial hypertension (PR 1.83, 95%, CI 1.10-3.04), polypharmacy (PR 3.12, 95%, CI 2.17-4.50), and diabetes mellitus (PR 0.60, 95%, CI 0.45-0.81). The risk factors for the occurrence of drug interaction were the presence of diabetes mellitus, hypertension, and polypharmacy.